The Influence of TikTok Social Media Influencers, Brand Image, and Lifestyle on Purchase Interest of Avoskin Skincare Products in Batam City - Fadilla Elsabila; Inda Sukati (Economics and Digital Business Review, 2026)
This study aims to analyze the influence of TikTok social media influencers, brand image, and lifestyle on consumers' purchase intention toward Avoskin skincare products in Batam City. The research is motivated by the rapid growth of TikTok as a digital marketing platform that is widely utilized by companies to attract consumer interest in skincare products. This study employed a quantitative approach with descriptive and verificative methods. Data were collected through questionnaires distributed to 116 respondents who were residents of Batam City, at least 17 years old, active TikTok users, and familiar with Avoskin products. Data analysis was conducted using SPSS through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results indicate that all research instruments are valid, reliable, and meet the classical assumption requirements. Partially, TikTok social media influencers have a positive and significant effect on purchase intention with a significance value of <0.001, brand image has a positive and significant effect with a significance value of 0.036, and lifestyle has a positive and significant effect with a significance value of <0.001. Simultaneously, the three variables have a positive and significant effect on purchase intention with a significance value of <0.001. The coefficient of determination (R²) value of 0.693 indicates that 69.3% of the variation in purchase intention can be explained by TikTok social media influencers, brand image, and lifestyle. These findings demonstrate that the three factors play an important role in increasing consumers’ purchase intention toward Avoskin skincare products in Batam City.